Methodology to qualify marine electrical propulsion system architectures for platform supply vessels. Issue 2 (1st June 2018) - Kamala, Srinivasarao; Chauhan, Priyesh J.; Panda, Sanjib K.; Wilson, Gary; Liu, Xiong; Gupta, Amit K.
Abstract : Conventional diesel‐electric propulsion systems in platform supply vessels (PSVs) use low‐voltage AC (LVAC) supply‐based architecture with multiple diesel‐generators feeding busbars at 690 V, 60 Hz. The busbars distribute power to thruster motor drives via multi‐pulse transformers and diode bridge rectifiers. Advancements in electrical power conversion and distribution technologies offer possibilities of AC or DC distribution at low/medium voltage (LV/MV) for reduced fuel consumption (FC), emissions, and equipment footprint. This study presents methodology to qualify propulsion system architecture for PSV application. Potential architectures, besides conventional one, are active front end (AFE) converter‐based LVAC (690 V), MVAC (3.3 kV), LVDC (1000 V), and MVDC (5000 V). Performances of these architectures are assessed quantitatively based on FC, emissions, weight, volume, efficiency, and reliability. FC is estimated based on brake‐specific FC data of diesel engine. N O x, S O 2, and C O 2 emissions are assessed based on their emission factors. The weight, volume, and efficiency are estimated based on parameters of individual components. Reliability is assessed based on component failure data using DIgSILENT Power Factory. The architectures are ranked based on performance parameters using a Pugh matrix. The most suitable architecture for the target PSV is LVDC, followed by MVDC, LVAC with AFE, MVAC, and conventional LVAC.